2015
DOI: 10.3732/ajb.1400517
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics and pollen ultrastructure in Ephedra

Abstract: The fast Ut and dense ultrastructure of E. foeminea pollen are consistent with functional traits that distinguish entomophilous species from anemophilous species. In anemophilous Ephedra species, ovulate organs create an aerodynamic microenvironment that directs airborne pollen to the pollination drops. In E. foeminea, no such microenvironment is created. Ephedroid palynomorphs from the Cretaceous share the ultrastructural characteristics of E. foeminea, and at least some may, therefore, have been produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 57 publications
(114 reference statements)
0
48
0
8
Order By: Relevance
“…Although Ephedra pollen is typically described as inaperturate (Erdtman 1952;Huynh 1975;Kurmann & Zavada 1994;El-Ghazaly et al 1998;Ickert-Bond et al 2003;Doores et al 2007), some authors have interpreted Ephedra pollen as polyaperturate (Steeves & Barghoorn 1959;Bharadwaj 1963), referring to the furrows that run between the plicae parallel to the long equatorial axis. In these furrows, which have been called hyaline lines (Woodhouse 1935;Steeves & Barghoorn 1959;Kedves 1987;Kurmann & Zavada 1994;El-Ghazaly et al 1998), pseudosulci (Huynh 1975;Bolinder et al 2015) and colpi (Steeves & Barghoorn 1959;Zhang & Xi 1983), the exine is much thinner than over the ridges and neither the tectum nor the infratectum is present (Osborn 2000;Tekleva & Krassilov 2009;Bolinder et al 2015). When the pollen germinates, the exine splits open in two of these furrows and detaches from the intine (Land 1907;Mehra 1938;El-Ghazaly et al 1998), and, based on the polarity described by Huynh (1975) and El-Ghazaly et al (1998), we will hereafter refer to the furrows as pseudosulci (Figure 1) (following Huynh 1975;Bolinder et al 2015).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Although Ephedra pollen is typically described as inaperturate (Erdtman 1952;Huynh 1975;Kurmann & Zavada 1994;El-Ghazaly et al 1998;Ickert-Bond et al 2003;Doores et al 2007), some authors have interpreted Ephedra pollen as polyaperturate (Steeves & Barghoorn 1959;Bharadwaj 1963), referring to the furrows that run between the plicae parallel to the long equatorial axis. In these furrows, which have been called hyaline lines (Woodhouse 1935;Steeves & Barghoorn 1959;Kedves 1987;Kurmann & Zavada 1994;El-Ghazaly et al 1998), pseudosulci (Huynh 1975;Bolinder et al 2015) and colpi (Steeves & Barghoorn 1959;Zhang & Xi 1983), the exine is much thinner than over the ridges and neither the tectum nor the infratectum is present (Osborn 2000;Tekleva & Krassilov 2009;Bolinder et al 2015). When the pollen germinates, the exine splits open in two of these furrows and detaches from the intine (Land 1907;Mehra 1938;El-Ghazaly et al 1998), and, based on the polarity described by Huynh (1975) and El-Ghazaly et al (1998), we will hereafter refer to the furrows as pseudosulci (Figure 1) (following Huynh 1975;Bolinder et al 2015).…”
mentioning
confidence: 97%
“…Ephedra pollen is large, between 34 and 81 µm in its longest (equatorial) diameter (Steeves & Barghoorn 1959), and, as in remaining Gnetales, the pollen wall consists of a homogenous tectum, a granular infratectum of varying density, and a thin foot layer adnate to a distinct lamellar endexine (Gullvåg 1966;Van Campo & Lugardon 1973;Hesse 1984;Zavada 1984;Kurmann 1992;Rowley 1995;ElGhazaly & Rowley 1997;Osborn 2000;Tekleva & Krassilov 2009;Bolinder et al 2015). Based on developmental studies, Huynh (1975) and ElGhazaly et al (1998) concluded that the longest axis in Ephedra pollen is equatorial and the polar axis is equal to one of the shortest axes (Huynh 1975;El-Ghazaly et al 1998) (Figure 1).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Insect pollination is conceivably the ancestral state in the Gnetales (figure 1a). The sister species of the remaining Ephedra, Ephedra foeminea [5], is insect-pollinated [3,8,9], as are Welwitschia [10] and Gnetum [11] (Gnetales), and probably also Ephedra aphylla [12]. By contrast, other species of Ephedra are considered wind-pollinated [13] although this has only been rigorously tested for Ephedra distachya [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…The sister species of the remaining Ephedra, Ephedra foeminea [5], is insect-pollinated [3,8,9], as are Welwitschia [10] and Gnetum [11] (Gnetales), and probably also Ephedra aphylla [12]. By contrast, other species of Ephedra are considered wind-pollinated [13] although this has only been rigorously tested for Ephedra distachya [3,9]. As most gymnosperms, Ephedra produces liquid by secretion from the nucellus [6,14], and the liquid is exposed as a pollination drop at the micropylar opening (figure 1b,c).…”
Section: Introductionmentioning
confidence: 99%